2018
DOI: 10.1186/s13071-018-3095-y
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and phylogenetic relationships of European species of Crepidostomum Braun, 1900 (Trematoda: Allocreadiidae) based on rDNA, with special reference to Crepidostomum oschmarini Zhokhov & Pugacheva, 1998

Abstract: BackgroundWithin the genus Crepidostomum Braun, 1900, identification of species and taxonomic decisions made only on the basis of adult morphology have resulted in great problems associated with evaluating actual diversity and validity of species. Life-cycle data, while equal in importance to adult characters, are scarce, controversial or incomplete for most Crepidostomum spp. In this study, rDNA sequences generated from adult and larval Crepidostomum spp. and some other allocreadiid species were analysed to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 40 publications
(83 reference statements)
3
13
0
Order By: Relevance
“…Furthermore, if we accept that the only species of the genus for which molecular data are available, C. funduli , from fundulids in USA, is actually a member of the genus (see contrary opinions in Manter, 1962; Brooks, 1976), then molecular phylogenetic analyses shed light on the paraphyly of Creptotrema . Other studies have already demonstrated, through molecular analyses of the 28S rRNA gene, cases of paraphyletic genera within Allocreadiidae, which contrast with the morphological concept on which these genera were erected (see Atopkin & Shedko, 2014; Pérez-Ponce de León et al , 2016; Petkevičiūtė, 2018). Recent molecular phylogenetic analyses of the Allocreadiidae show that the ‘papillose allocreadiids’ ( sensu Hopkins, 1937) do not form a monophyletic assemblage; oral lobes apparently either arose or were secondarily lost several times during the evolutionary history of the group, depending on the plesiomorphic condition (see Hernández-Mena et al ., 2016, 2019; Pérez-Ponce de León et al ., 2016; Atopkin et al ., 2020).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, if we accept that the only species of the genus for which molecular data are available, C. funduli , from fundulids in USA, is actually a member of the genus (see contrary opinions in Manter, 1962; Brooks, 1976), then molecular phylogenetic analyses shed light on the paraphyly of Creptotrema . Other studies have already demonstrated, through molecular analyses of the 28S rRNA gene, cases of paraphyletic genera within Allocreadiidae, which contrast with the morphological concept on which these genera were erected (see Atopkin & Shedko, 2014; Pérez-Ponce de León et al , 2016; Petkevičiūtė, 2018). Recent molecular phylogenetic analyses of the Allocreadiidae show that the ‘papillose allocreadiids’ ( sensu Hopkins, 1937) do not form a monophyletic assemblage; oral lobes apparently either arose or were secondarily lost several times during the evolutionary history of the group, depending on the plesiomorphic condition (see Hernández-Mena et al ., 2016, 2019; Pérez-Ponce de León et al ., 2016; Atopkin et al ., 2020).…”
Section: Discussionmentioning
confidence: 97%
“…In the case of allocreadiid trematodes, several authors have shown that SEM is an invaluable tool to accurately discern the presence and shape of structures such as muscular lobes on the oral sucker and papillae distribution (e.g. Caira, 1989; Choudhury & Nelson, 2000; Razo-Mendivil et al ., 2014; Hernández-Mena et al ., 2016; Petkevičiūtė, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…DNA fragments spanning the 3′ end of the 5.8S rRNA gene, the complete internal transcribed spacer 2 region (ITS2) and a small section at the 5′ end of the 28S gene were amplified using universal primers for flatworms, the forward primer 3S (5′-CGG TGG ATC ACT CGG CTC GTG-3′) (Bowles et al ., 1995) and the reverse primer ITS2.2 (5′-CCT GGT TAG TTT CTT TTC CTC CGC-3′) (Cribb et al ., 1998). Primer pair AlJe-F (5′-GTC TGG CTT GGC AGT TCT A-3′) and AlJe-R (5′-CTG CCC AAT TTG ACC AAG C-3′), designed for species of the Allocreadiidae (Petkevičiūtė et al ., 2018b)), was suitable to amplify the end of the internal transcribed spacer 1 (ITS1), the complete 5.8S rDNA and ITS2, and also a small section at the 5′ end of the 28S gene of A. progenetica . A fragment at the 5′ end of the 28S rRNA gene was amplified using the forward primers Digl2 (5′-AAG CAT ATC ACT AAG CGG-3′) (Tkach et al ., 2003) or ZX-1 (5′-ACC CGC TGA ATT TAA GCA TAT-3′) (Bray et al ., 2009) and the reverse primers L0 (5′-GCT ATC CTG AG (AG) GAA ACT TCG-3′) (Tkach et al ., 1999) or 1500R (5′-GCT ATC CTG AGG GAA ACT TCG-3′) (Olson et al ., 2003; Tkach et al ., 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Crepidostomum spp. have Radix and Pisidium as first intermediate hosts, mayflies (Ephemeroptera) and amphipods (Gammarus) as second intermediate hosts, and trout as a final host (Awachie 1968;Petkevičiūtė et al 2018). In a study from North Wales, Awachie (1968) found Radix peregra (Müller, 1774) as the first intermediate host of C. metoecus, the most numerous of the two Crepidostomum species infecting brown trout in Øvre Heimdalsvatn, and Gammarus pulex (Linnaeus, 1758) was described as the second intermediate host.…”
Section: Capillaria Spmentioning
confidence: 99%
“…In a study from North Wales, Awachie (1968) found Radix peregra (Müller, 1774) as the first intermediate host of C. metoecus, the most numerous of the two Crepidostomum species infecting brown trout in Øvre Heimdalsvatn, and Gammarus pulex (Linnaeus, 1758) was described as the second intermediate host. Petkevičiūtė et al (2018) referred however to a study where Pisidium was recorded as the first intermediate host, and nymphs of the mayfly genus Ameletus Eaton, 1865 as second intermediate host of C. metoecus. Thus, most probably several species of molluscs, gastropods, and mayflies are candidates for first or second intermediate hosts of the Crepidostomum species.…”
Section: Capillaria Spmentioning
confidence: 99%